Box–Behnken Design-Based Optimization of Extraction Parameters of Phenolics, Antioxidant Activity, and In Vitro Bioactive and Cytotoxic Properties of Rhus typhina Fruits - Maria Denisa Cocîrlea; Natalia Simionescu; Teodora Călin; Florentina Gatea; Georgiana Ileana Badea; Emanuel Vamanu; Simona Oancea (Applied Sciences)
Rhus typhina, an invasive plant species, contains valuable compounds that can be utilized in various fields. The main aim of this paper was to find the optimal conditions for extracting high amounts of bioactive compounds from R. typhina fruits using ultrasound-assisted and bead-beating techniques under different parameters (solvent concentration, solvent/solid ratio, extraction time, bead size, and material). A Box–Behnken design was applied for ultrasound-assisted extraction. The following process parameters were found to be optimal: 20/1 solvent/solid ratio (v/w), 61.51% aqueous ethanol, 10 min extraction time, with a composite desirability of 0.7719. The HPLC profile indicates that p-coumaric acid was the most abundant phenolic compound found in the BBE extract. The BBE extract was subjected to in vitro biological tests. The results indicate a high antimicrobial activity on Streptococcus pyogenes (20 mm inhibition zone) and Salmonella enterica (12 mm inhibition zone). A hemolysis rate of 19.85% was found at an extract concentration of 1000 µg/mL on sheep erythrocytes. We report for the first time the protective role of the extract on cell viability of human gingival fibroblasts, but also a weak antiproliferative effect on the HepG2 human liver cancer cell line. Overall, we conclude that R. typhina fruits are rich in bioactive compounds that can be recovered using proper extraction conditions. Further research is required to understand and valorize their biological potential.